A clinical case of the retroaortal course of the circumflex artery from the right coronary artery - E. A. Zakharyan; P. E. Grigoriev; D. V. Shatov; O. V. Soldatova; A. V. Fedorets; L. E. Kapitanova (Бюллетень сибирской медицины, 2023)
An anomalous course of coronary arteries is fairly rare pathology, which, however, may underlie clinical manifestations of coronary artery disease. Expanding the possibilities of diagnostic coronary angiography makes it possible to detect numerous types of congenital anomalies of the coronary arteries.However, if earlier they were considered as angiographic findings and were characterized as benign, now this attitude has been changed due to reports of cases of syncope, angina pectoris, and sudden cardiac death associated with their presence. In this regard, a trend emerged to consider such anomalies as “potentially malignant”, which explains special caution at their detection. The article presents a clinical case of an anomalous retroaortic course of the circumflex artery from the right coronary artery.